Identification of VASA gene expression in in-vitro culture from non-obstructive azoospermia (NOA) testicular biopsy cells: A study to unlock knowledge of male infertility - Abdul Razak, Redzuan Nul Hakim; Md Isa, Muhammad Lokman; Muhammad Razali, Refaudeen; Mat Yusof, Afzan; Abdul Wahab, Azantee Yazmie; Ahmad Arifin, Syamsul; Ramli, Roszaman; Muhammad, Husin (International Islamic University Malaysia, 2018)
The expression product of VASA gene is widely conserved germ line marker and participates to regulate the development of reproductive system and spermatogenesis in healthy man. Azoospermic is a condition which the man is unable to produce any sperm cells for reproduction activity. This condition produced has bad impact to the man since the ability to produce their own progeny will be interrupted or blocked forever. Not only the family bloodline of the man would be ended, the psychological issue like shamefulness and low self-esteem occurs. In Islam, seeking knowledge is an obligatory to Muslims in order to solve problems and improve lives. Thus to unveil the problem of azoospermic man we aimed to determine the level of VASA gene expression in samples of testes cells of non-obstructive azoospermic (NOA) and compare it with sperms of healthy man. Samples were taken from three NOA patients by testicular sperm extraction (TESE) to obtain testicular biopsies. Testicular cells were isolated and cultured in supplemented knockout DMEM media. VASA gene expression was determined by reverse transcriptase polymerase chain reaction (RT-PCR). The VASA gene expression from sperm of healthy man was also determined for comparison purpose. It was demonstrated that the addition of growth factor significantly increased SSC-like cells colony formation in tissues obtained from NOA patients. No VASA expression was detected in spermatogonial-like stem cells culture on day 1, 7, 14 and 21 in each of the azoospermic samples. Our findings shown VASA gene was not expressed in spermatogenesis in vitro culture that might be associated with the abnormal differentiation of primordial germ cells that lead to male infertility. Islam also teaches us to not have feelings of despair and for problems that we are facing but to find the solution and consider the problem as a test from the Almighty. All the tests should be handled with strong believe since only Allah (SWT) knows what the best for us and each of the tests will have justified wisdom and benefits which we as human being are unable to realise thoroughly.